Prevalence of the N-Acetyltransferase (NAT2) gene polymorphism 282C>T in Peruvian population and health implications - Salazar-Granara, Alberto (2016)
Objective: To determine the frequency of the C282T polymorphism of the NAT2 gene (N acetyltransferase) in Peruvian populations. Field work, focused on exploring genetic risk factor in Peruvian populations, which has influence in the response to drugs and malignancies aetiology. Material and Methods: Cross-sectional study. 166 voluntaries from Lima, Lambayeque, Apurimac, Puno, San Martin, Amazonas and Loreto were enrolled. The sampling was done by convenience and it was use the RFLP-PCR conventional technique was used. Results: The allele frequency were 54% (n=126) for C282 and 46% (n=106) for T282. For the T allele, by its orign , stand out 2 those which origins were Lima 42% (n=25), Amazonas 47% (n=16), San Martin 74% (n=28) and Apurimac 50% (n=13) (X , p>0.05). A global genotype frequency were 26.7% (n=31) for C282/C282, 56.0% (n=65) for C282/T282 and 17.2% (n=20) for T282/T282 (Hardy Weinberg Test p>0.05). By origin, Puno presented allelic imbalance (Hardy Weinberg test p<0.05) and the others populations presented allelic balance (Hardy Weinberg test p>0.05). Conclusion: The overall frequency of NAT2 allele T282 was 46%; San Martin had the highest prevalence (74%). The T282 allele is linked to neoplastic diseases and adverse reactions to anti-TB drugs, these results will be used for the application of pharmacogenetics in Peru.